91 How the tracey judgement has changed dnacpr discussions in palliative care. Issue Volume 8: Issue (2018)Supplement 1 (1st March 2018) - Macfarlane, Mike; Shayler, Steph; Nelms, Louisa; Cares, WM; Willis, Derek
Abstract : Background: The decision published from the Court of Appeal of England and Wales in 2014 in the case of Tracey vs Cambridge University Hospital ( 'the Tracey judgement') changed the requirements for discussing Do Not Attempt Cardiopulmonary Resuscitation (DNACPR) decisions with patients. Methods: A retrospective case note review aiming to identify changes in practice when discussing DNACPR decisions following the Tracey judgement. 150 case notes from 2013 (before the Tracey judgement) were compared with 150 case notes from 2015 (following the Tracey judgement) at five hospices in the West Midlands. The notes were analysed to identify whether the judgement had resulted in a change in how frequently DNACPR decisions were discussed with patients or their families, as well as any changes in the rationale for not discussing such decisions. Results: Discussions with patients increased from 31% to 60% and with relatives from 29% to 59%. The most common reason that DNACPR decisions were not discussed with patients or relatives changed from a belief that these discussions would cause distress in 2013 (23%) to the patient lacking capacity to engage in such discussions in 2015 (40%). There was a lack of consistency and clarity in defining the concept of 'physical or psychological harm' following the Tracey judgement. Conclusion: Healthcare professionals specialising in palliative care in the region and time frame studied are discussing DNACPR decisions more frequently with patients and families following the Tracey judgement but clarity on what constitutes 'physical or psychological harm' caused by these discussions is still required.